Development of the Human Circulatory System Module to Support Junior High School Students' Independent Learning - Nurfitriah, Alfi Sholichatur Rohmah (Islamic Journal of Integrated Science Education (IJISE), 2023)
This research is to produce a teaching material product or science learning module about human circulatory system that is suitable to support junior high school students’ independent learning by fulfilling eligibility and effectiveness. This research uses the Borg and Gall research model which is modified into 7 stages. This type of research is Research and Development (R & D). Techniques for collecting data used observation, questionnaires for expert and student validation sheets, interviews. Module validity, curriculum validity, material validity were validated by several teachers in science subjects at Junior High School 1 Papar. The research results show that the assessment of material experts with an average score of 3.76 with very good criteria and the assessment of module experts get approximately a score of 3.76 with very good criteria. The results of the assessment in the initial field trials obtained a percentage of 90.23% with the criteria of feasible and the results of the field trials obtained a percentage of 97.79% with the criteria of eligible. Based on the results of the research, it can be concluded that the science module on the subject of the human circulatory system is suitable for use as teaching material or a module that students can use in independent learning and has met its feasibility and effectiveness.